2020
DOI: 10.14710/jp.19.1.1-14
|View full text |Cite
|
Sign up to set email alerts
|

Career Decision-Making Attribution and Self Efficacy: The Moderating Role of Emotional Intelligence

Abstract: It is known that gifted high-school students tend to have difficulty in choosing career due to their wide-range interests and capabilities. In order to successfully making an appropriate career choice, having a high level of career decision making self-efficacy (CDMSE) is an important precondition. CDMSE is the belief in one’s ability to successfully complete the task necessary to make career-related decisions. Of several factors known to be affecting CDMSE, previous study has shown that career decision-making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
(47 reference statements)
1
6
0
1
Order By: Relevance
“…The researcher believes that high school students show the ability to recognize the feelings of their colleagues, recognize their needs and meet them, benefit from the diversity of their friends and have the ability to understand, sympathize and negotiate with their friends, and the ability to establish social relationships, and these sincere feelings help students to succeed, and pay attention to the accurate indicators that denotes the feelings of the other person. This result is in agreement with the result of the study (Misron, & Hee, 2021), which showed that emotional intelligence significantly mediates the relationship between the five major personality traits and customer-directed behavior, and it agrees with the result of the study (Salim, & Safitri, 2020), which showed that emotional intelligence can Act as a predictor of self-efficacy in professional decision-making.…”
Section: Results Related To First Question: What Is Emotional Intelligence Level For Secondary School Students Insupporting
confidence: 92%
See 2 more Smart Citations
“…The researcher believes that high school students show the ability to recognize the feelings of their colleagues, recognize their needs and meet them, benefit from the diversity of their friends and have the ability to understand, sympathize and negotiate with their friends, and the ability to establish social relationships, and these sincere feelings help students to succeed, and pay attention to the accurate indicators that denotes the feelings of the other person. This result is in agreement with the result of the study (Misron, & Hee, 2021), which showed that emotional intelligence significantly mediates the relationship between the five major personality traits and customer-directed behavior, and it agrees with the result of the study (Salim, & Safitri, 2020), which showed that emotional intelligence can Act as a predictor of self-efficacy in professional decision-making.…”
Section: Results Related To First Question: What Is Emotional Intelligence Level For Secondary School Students Insupporting
confidence: 92%
“…Emotional intelligence characterizes its owner that the greater his ability to control the emotions of others, the more his need to know about the world around him, and his aspiration for something new, the more clear his creative direction (Lee, 2019). Affective intelligence includes in its structure the appropriate cognitive, behavioral, and emotional components that provide awareness, understanding, and regulation of the emotions of the individual and the emotions of others (Carmeli, 2003), and its impact on the success of interactions and the personal development of students (Salim, & Safitri, 2020)), and it is considered a psychological characteristic that forms the basis of a group A wide range of professional competencies, the existence of which is a criterion for assessing a student as a future professional on a large scale in his profession . Developing emotional competence makes a person more professional and professionally more human (Olowookere, et, al, 2020).…”
Section: Theoretical Framework Emotional Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“… 1 In building a career, self-awareness is compulsory, that what the person actually wants to achieve in their lives and then accordingly making plans and working on them to achieve them. 2 The significance of this study was to understand the role of emotional intelligence and generalized self-efficacy on career decision-making difficulties among university students. The study goal was to see the impact of emotional intelligence on career decision-making difficulties, and GSE among university students in China.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In building a career, self-awareness is compulsory, that is what the person actually wants to achieve in their lives and then accordingly making plans and working to achieve them. 2 As per Di Fabio and Kenny, 3 university time requires major decisions to continue the education based upon the plan of joining a particular workforce where students have high expectations for themselves, ie, about careers, etc., and they are directly influencing the social progress, sustainability, and resilience of their communities and nations. For many students, the career decision-making process is a major life task and, obviously, it can raise uncertainties that may lead to delays in making career decisions.…”
Section: Introductionmentioning
confidence: 99%